Hsf transcription factor gene family in peanut (Arachis hypogaea L.): genome-wide characterization and expression analysis under drought and salt stresses - Wang, Qi; Zhang, Zhenbiao; Guo, Cun; Zhao, Xiaobo; Li, Zhiyuan; Mou, Yifei; Sun, Quanxi; Wang, Juan; Yuan, Cuiling; Li, Chunjuan; Cong, Ping; Shan, Shihua (Frontiers in Plant Science, 2023)
Heat shock transcription factors (Hsfs) play important roles in plant developmental regulations and various stress responses. In present study, 46 Hsf genes in peanut (AhHsf) were identified and analyzed. The 46 AhHsf genes were classed into three groups (A, B, and C) and 14 subgroups (A1-A9, B1-B4, and C1) together with their Arabidopsis homologs according to phylogenetic analyses, and 46 AhHsf genes unequally located on 17 chromosomes. Gene structure and protein motif analysis revealed that members from the same subgroup possessed similar exon/intron and motif organization, further supporting the results of phylogenetic analyses. Gene duplication events were found in peanut Hsf gene family via syntenic analysis, which were important in Hsf gene family expansion in peanut. We found that the expression of AhHsf genes were detected in different tissues using published data, implying that AhHsf genes may differ in function. In addition, several AhHsf genes (AhHsf5, AhHsf11, AhHsf20, AhHsf24, AhHsf30, AhHsf35) were induced by drought and salt stresses. Furthermore, the stress-induced member AhHsf20 was found to be located in nucleus. Notably, overexpression of AhHsf20 was able to enhance salt tolerance. These results from this study may provide valuable information for further functional analysis of peanut Hsf genes.